Primary lung cancer in children and adolescents: Analysis of a surveillance, epidemiology, and end results database - Shao, Weipeng; Liu, Jie; Li, Bobo; Guo, Xiaokang; Sun, Jian; Li, Hui; Guo, Hongbo (Frontiers in Oncology, 2023)
Background: The incidence of primary lung cancer (LC) in children and adolescence was rare. We analyzed data from a SEER database to better define the incidence, clinical characters, pathology, treatment, and outcomes of rare primary malignant pulmonary tumors in childhood and adolescence. Methods: Patients were chosen from the SEER database (SEER*Stat 8.4.0 software) from 2000 to 2019 and all patients were pathologically diagnosed with primary malignant tumors of the lung and bronchus. Demographic characteristics of patients (age, gender, race, primary site, laterality, location, differentiation grade, operation methods, histology, and history of radiotherapy and chemotherapy), as well as TNM stage and survival time, were collected. Results: A total of 301 cases of children ≤19 years of age with a primary malignant pulmonary tumor were reported to the SEER database from 2000 to 2019. There were 143 men (47.5%) and 158 women (52.5%). As for the primary site, the main site was the lower lobe (33.2%), followed by the upper lobe (26.9%). Lobectomy (39.9%) is the main operation method. Only 28 (9.3%) patients received radiotherapy and 112 (37.2) patients received chemotherapy. Carcinoid tumor was the most common histology (29.6%), followed by pulmonary blastoma (PB) (22.3%), mucoepidermoid carcinoma (MEC) (12.3%), adenocarcinoma (10.3%). The mean follow-up time was 100 months. For the entire group of children and adolescents, the 1-year OS was 89.1%, and the 3-year overall survival (OS) was 79.7%. the 5-year OS was 77.9%, the 10-year OS was 75.7%, and the 15-year OS was 73.9%. And 1-year lung cancer specificity survival (LCSS) was 89.8%, and the 3-year LCSS was 80.4%. the 5-year LCSS was 79.4%, the 10-year LCSS was 77.7%, and the 15-year LCSS was 75.9%. The OS of atypical carcinoma, carcinoid tumor, and MEC were in the top three. Conclusions: Primary LC in children and adolescent were rare and histopathological diverse. Fortunately, children and adolescents with LC had an overall favorable outcome after treatment. Histology, differentiation grade, surgery, TNM stage, and therapeutic modalities have important influence on OS. The further treatment experience of each pathological type would make better evidence-based practice possible.